Modern weapons and military equipment for issue 1-2016 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Bomber battle Abrams tank to soon get Advanced multi-purpose 120 mm rounds ST Kinetics unveils next generation Terrex 2 amphibious armoured vehicle Poland’s Rosomak range extended Nexter pins export hopes on VBCI-2 China unveils next gen Wing Long II armed UAV China showcases new weapon systems at 3 September parade UAE may have acquired long-range SeaHake mod 4 ER torpedo vessels Taiwan unveils advanced self-propelled MMS US military ramps up directed energy efforts MBT developments heads eastwards